Whole grains temper immune-mediated inflammation in Chinese esophageal squamous-cell carcinoma survivors: a multicenter questionnaire study - Ren, Ya-Qiong; Wang, Yuxiang; Li, Yang; Li, Lei; Guo, You; Zhang, Ning-Gang (Frontiers in Immunology, 2025)
ObjectivesTo examine whether habitual whole-grain intake is associated with lower patient-reported systemic inflammatory distress among ambulatory survivors of esophageal squamous-cell carcinoma (ESCC).MethodsWe conducted a cross-sectional questionnaire study (May 2023–July 2025) at four tertiary hospitals in Shanxi Province among adults with stage I–IIIA ESCC (n = 392). A validated semi-quantitative food frequency questionnaire quantified five whole-grain categories. Exposures were modeled as grams/day-¹ (sex-specific quartiles; continuous per 10 g), an energy-adjusted density metric (g/1,000 kcal), and a diversity score (0–5 categories consumed ≥ once/week). Systemic inflammatory symptoms were measured with the seven-item Inflammation Distress Index (IDI). Multivariable logistic models estimated adjusted odds ratios (aORs) for elevated IDI (≥ 10); γ-log generalized linear models analyzed continuous IDI; restricted cubic splines assessed dose–response. Models adjusted for sociodemographic, clinical, and behavioral covariates, with total energy included when grams were exposed.ResultsMedian whole-grain intake was 35.4 g/day-¹ (IQR 22.1–58.7); 28.1% had elevated IDI. Prevalence declined across quartiles (39.8%, 34.7%, 25.5%, 12.2%). Fully adjusted aORs (vs. Q1) were 0.95 (0.62–1.47), 0.49 (0.31–0.76), and 0.19 (0.11–0.33) for Q2–Q4 (p-trend < 0.001). Each 10 g/day-¹ increment corresponded to a 6% lower mean IDI (mean ratio 0.94; 0.92–0.96). Splines showed a steep inverse slope up to ~60 g/day-¹ with a plateau (p-nonlinearity = 0.031). Findings were consistent by stage (interaction p = 0.59) and smoking status (p = 0.67), robust in sensitivity analyses, and supported by density (Q4 vs. Q1 aOR 0.21; per +5 g/1,000 kcal-¹ aOR 0.93) and diversity (per +1 category aOR 0.86; ≥ 3 vs. 0–1 aOR 0.48) metrics.ConclusionIn Shanxi ESCC survivorship care, higher whole-grain intake—particularly ~50 g/day-¹ and with greater variety—aligns with substantially lower systemic inflammatory distress, supporting grain-centered dietary counseling.